A low-tortuosity thick electrode and its preparation method and application
By using a mixing and heat treatment technology of porous adhesive and electrode active material in thick electrodes, a uniform pore structure is formed, which solves the problem of lithium ion transmission in the liquid phase of thick electrodes, and significantly improves the rate performance and cycling performance of the battery.
Patent Information
- Application Number
- CN202211091041.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-09-07
AI Technical Summary
In the prior art, the liquid phase lithium ion transmission of thick electrodes is hindered, resulting in an increase in internal resistance, a decrease in the utilization rate of active materials, and a significant attenuation of circulation and rate performance.
A porous binder is used to mix with the electrode active material, and a uniform pore structure is formed by dry coating and heat treatment, which reduces the electrode tortuousness and improves the liquid phase transfer efficiency of the electrolyte.
Significantly reduce the tortuousness of the thick electrode, improve the liquid phase transmission efficiency of the electrolyte, enhance the peel strength of the electrode sheet, and improve the rate performance and circulation performance of the thick electrode.
Smart Images

Figure CN115312777B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a low-tortuosity thick electrode and a preparation method and application thereof. Background Art
[0002] In lithium-ion batteries, as the thickness of the positive and / or negative electrodes of the battery increases, the proportion of active materials also increases significantly, which can significantly increase the energy density of the single battery. Therefore, the development of thick electrodes is of great significance to improving the energy density of batteries. However, as the thickness of the electrode increases, the liquid-phase lithium ion transmission of the pole piece is significantly hindered, resulting in an increase in the internal resistance of the battery, a significant decrease in the utilization rate of active materials, and a significant attenuation of the cycle performance and rate performance. Therefore, increasing and improving the liquid-phase transmission rate of thick electrodes is an important method and means to improve the kinetic performance of thick electrodes.
[0003] At present, the main methods used are pole piece pore making, double-layer coating and external physical field to regulate the pore structure of thick electrodes and improve their dynamic performance. Patent CN104157827A discloses a lithium-ion battery negative electrode sheet, which is prepared by dissolving a thickener in a solvent, adding a pore-forming agent, a conductive agent, a negative electrode active material and a binder to obtain an active slurry, and coating the active slurry on a current collector to obtain a lithium-ion battery negative electrode sheet. The pore-forming effect of the pore-forming agent improves the infiltration ability of lithium ions. Patent CN114273510A discloses a pore-forming roller and a method and application for improving the porosity of a pole piece. The pore-forming roller includes a roller body and pore-forming nails distributed on the surface of the roller body. The pore-forming roller is used to make holes on the surface of the pole piece. The existing battery production process does not need to be changed to achieve the regulation of the pole piece porosity, which greatly improves the infiltration performance of the pole piece to the electrolyte. Double-layer coating mainly achieves pore gradient control of the upper and lower layers by using main materials with different particle sizes, such as patent CN112271270B, which shortens the transmission path of lithium ions and improves the wetting performance of the electrolyte by arranging at least two layers of membranes with different active material particle sizes on the current collector.
[0004] In the prior art, the use of pole piece pore making, double-layer coating and other methods can effectively improve the dynamic performance of thick electrodes, but the above solutions all have certain disadvantages: low pole piece pore making production efficiency, large investment in pore making equipment, uneven pores, residual pore-forming agent leading to battery performance degradation, etc., and are still in the experimental verification stage. During the preparation process of double-layer coated electrodes, two sets of slurry systems and feeding systems are required, and a double-layer simultaneous coating die is used. The matching requirements of the upper and lower slurries are high, the coating stability is difficult to control, and the equipment investment is also high. Therefore, it is of great significance to provide a thick electrode with low preparation cost, uniform pole piece pore distribution, high electrode liquid phase transmission rate, and both rate performance and cycle performance. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a low-tortuosity thick electrode and its preparation method and application. The thick electrode of the present invention contains a porous binder, and the binder with a porous structure can improve the mixing uniformity with the electrode active material, reduce the internal resistance, and improve the rate performance. After heat treatment, it is in full contact with the electrode active material, without binder migration, and can improve the peel strength of the electrode sheet; at the same time, the porous binder can form uniform pores after heat treatment, and the pores are uniform. The continuous through-hole structure formed by it can significantly reduce the tortuosity of the thick electrode and improve the liquid phase transmission efficiency of the electrolyte. The prepared low-tortuosity thick electrode has good rate performance and cycle performance.
[0006] In the present invention, "low tortuosity" means that the tortuosity of the thick electrode does not exceed 4.3. "Thick electrode" means that the thickness of the active coating on one side of the electrode is not less than 100 μm.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a low-tortuosity thick electrode, which includes a current collector and an active coating layer disposed on at least one side of the current collector, wherein the active coating layer includes an electrode active material and a porous binder.
[0009] The active coating layer of the low-tortuosity thick electrode of the present invention includes an electrode active material and a porous binder. By using a specific binder to prepare the thick electrode, the tortuosity of the thick electrode can be reduced, the liquid phase transmission efficiency of the electrolyte can be improved, and the peel strength of the electrode sheet can be improved, so that the low-tortuosity rear electrode has good rate performance and cycle performance. The technical principle is as follows:
[0010] First, the porous binder is evenly distributed in the active coating layer, and can form uniform pores after heat treatment, and the pores are uniformly formed; second, the porous structured binder is fully in contact with the electrode active material and other materials after hot melting, and there is no binder migration, which can significantly improve the electrode peeling strength and improve the cycle performance of the thick electrode; third, the porous binder can form a continuous through-hole structure, significantly reduce the tortuosity of the thick electrode, and improve the liquid phase transmission efficiency of the electrolyte; fourth, the porous binder can improve the mixing uniformity with the electrode active material, and the evenly mixed porous binder, electrode active material and evenly distributed pores can significantly reduce the internal resistance of the battery and improve the rate performance of the low-tortuosity thick electrode. The finally prepared low-tortuosity thick electrode has both good rate performance and cycle performance.
[0011] It should be noted that tortuosity is a well-known meaning in the art. The tortuosity represents the degree of curvature of the porous electrode transmission path, and the effective ion conductivity is inversely proportional to the tortuosity of the electrode; therefore, reducing the tortuosity of the electrode can improve the permeability of the electrolyte and the migration rate of ions.
[0012] Preferably, the thickness of the active coating layer on one side is 100-1000 μm, for example, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm or 1000 μm.
[0013] The low-tortuosity thick electrode of the present invention has good electrochemical performance, and still has excellent rate performance and cycle performance in a 100-1000 μm thick electrode.
[0014] Preferably, the median particle size of the porous binder is 1 to 50 μm, for example, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.
[0015] It should be noted that in the present invention, the median particle size is a well-known meaning in the art, also called the median particle size or average particle size Dv50, which is used to indicate the average particle size of the active material. The physical meaning is that particles smaller than the particle size account for 50% of the total volume of the particles, and particles larger than the particle size also account for 50% of the total volume of the particles. The median particle size can be conveniently measured using a laser particle size analyzer.
[0016] Preferably, the raw material of the porous binder includes any one or a combination of at least two of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylonitrile (PAN), guar gum and sodium alginate.
[0017] It should be noted that the low tortuosity thick electrode of the present invention can be a positive electrode or a negative electrode, and technicians in this field can select suitable raw materials for the porous binder according to the different electrodes; illustratively, when the low tortuosity thick electrode is a positive electrode, the porous binder can be prepared using PVDF, and when the low tortuosity thick electrode is a negative electrode, the porous binder can be prepared using CMC and SBR.
[0018] Preferably, the electrode active material includes a positive electrode active material or a negative electrode active material.
[0019] Exemplarily, when the low tortuosity thick electrode is the positive electrode, the electrode active material includes a positive electrode active material, and the positive electrode active material includes any one or a combination of at least two of lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), lithium nickel cobalt manganese oxide (NCM) and lithium nickel cobalt aluminum oxide (NCA), for example, it can be a combination of LCO and LMO, a combination of LFP and NCM, or a combination of LCO, LMO, LFP and NCA, etc.
[0020] Exemplarily, when the low tortuosity thick electrode is the negative electrode, the electrode active material includes a negative electrode active material, and the negative electrode active material includes any one or a combination of at least two of graphite, soft carbon, hard carbon, silicon carbon and silicon, for example, it can be a combination of graphite and silicon, a combination of soft carbon and hard carbon, a combination of graphite and silicon carbon, etc.
[0021] Preferably, the active coating layer also includes a conductive agent.
[0022] Preferably, the mass ratio of the electrode active material, the conductive agent and the porous binder is electrode active material: conductive agent: porous binder = (90-95): (1-3): (2-5), wherein the selection range of the electrode active material (90-95) can be, for example, 90, 91, 92, 93, 94 or 95, etc., the selection range of the conductive agent (1-3) can be, for example, 1, 1.5, 2, 2.5 or 3, etc., and the selection range of the porous binder (2-5) can be, for example, 2, 2.5, 3, 3.5, 4, 4.5 or 5, etc.
[0023] Preferably, the conductive agent includes any one of carbon black (SP), acetylene black (AB), carbon nanotubes (CNT), carbon fiber (CNF) and graphene, or a combination of at least two of them, for example, it can be a combination of SP and AB, a combination of SP and CNT, a combination of AB, CNT and graphene, or a combination of SP, AB, CNT, CNF and graphene, etc.
[0024] In a second aspect, the present invention provides a method for preparing a low-tortuosity thick electrode according to the first aspect, the preparation method comprising:
[0025] (1) mixing an electrode binder and a pore-forming agent, and granulating the mixture to obtain a porous binder;
[0026] (2) dry-mixing the electrode active material and the porous binder described in step (1) to obtain a mixed dry powder, and coating the mixed dry powder on at least one side surface of a current collector to obtain a thick electrode precursor;
[0027] (3) heat treating the thick electrode precursor described in step (2) to obtain a low-tortuosity thick electrode.
[0028] Thick electrode development is an important method and strategy to improve the energy density of lithium batteries. In order to improve the kinetic performance of thick electrodes, pores are made in the electrodes, which can significantly improve the electrolyte liquid phase transmission rate and reduce the internal resistance of the battery, thereby improving the thick electrode rate performance. However, conventional pore-forming agent pore-forming and laser pore-forming have many problems and shortcomings. The present invention provides a method for preparing a low-tortuosity thick electrode. Through the processes of preparing a porous binder, dry coating, and heat treatment of the electrode piece, the energy density and power density of the thick electrode are significantly improved, which has important application value in the field of thick electrode development.
[0029] In the present invention, a conventional electrode binder and a pore-forming agent are mixed and granulated, and micron-scale porous binder colloid particles are prepared through the pore-forming effect of the pore-forming agent. The prepared colloid particles have a rich pore structure, and the colloid particles are mixed with electrode active materials by a dry method and coated on the surface of a current collector, thereby improving the mixing uniformity of the binder and the electrode active material; finally, the thick electrode precursor obtained after coating is heat-treated to soften the porous binder into a molten state, and the softened porous binder is in full contact with the electrode active material and the current collector around it to form good internal bonding and interface contact, and at the same time, abundant through-pores are formed in the thick electrode, so that the electrode tortuosity is significantly reduced, which is beneficial to the liquid-phase lithium ion transmission of the thick electrode, thereby significantly improving the rate performance and cycle performance of the thick electrode.
[0030] In the present invention, dry mixing and dry coating processes are adopted, which can not only maintain the uniform pore structure of the porous binder and prevent the structural collapse and damage of the porous binder caused by the conventional wet slurry process, but also eliminate the electrode baking and pore making steps, greatly shortening the process time.
[0031] As a preferred technical solution of the preparation method of the present invention, the low tortuosity thick electrode is a positive electrode, and the mass of the pore-forming agent in step (1) accounts for 5 to 20% of the total mass of the electrode binder and the pore-forming agent, for example, it can be 5%, 6%, 8%, 10%, 12%, 14%, 16%, 18% or 20%, etc.
[0032] Preferably, the low-tortuosity thick electrode is a positive electrode, and the electrode binder comprises polyvinylidene fluoride.
[0033] As a preferred technical solution of the preparation method described in the present invention, the low tortuosity thick electrode is a negative electrode, and the mass ratio of the electrode binder and the pore-forming agent in step (1) is (25-50):(0.2-1), wherein the selection range of the electrode binder (25-50) can be, for example, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48 or 50, and the selection range of the pore-forming agent (0.2-1) can be, for example, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.
[0034] Preferably, the low tortuosity thick electrode is a negative electrode, and the electrode binder includes any one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylonitrile (PAN), guar gum and sodium alginate, or a combination of at least two thereof, such as a combination of CMC and SBR, a combination of PAA and SBR, a combination of sodium alginate and CMC, or a combination of PAA, PAN and SBR, etc.
[0035] Preferably, the low tortuosity thick electrode is a negative electrode, and the electrode binder comprises sodium carboxymethyl cellulose and styrene-butadiene rubber, and the mass ratio of the sodium carboxymethyl cellulose, styrene-butadiene rubber and pore-forming agent is (10-20):(15:30):(0.2-1), wherein the selection range of sodium carboxymethyl cellulose (10-20) can be, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20, etc., the selection range of styrene-butadiene rubber (15:30) can be, for example, 15, 16, 18, 20, 22, 25, 28 or 30, etc., and the selection range of the pore-forming agent (0.2-1) can be, for example, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.
[0036] In the present invention, by further optimizing the content of electrode binder and pore former in the low tortuosity thick electrode used as the positive electrode or negative electrode, a porous binder with better pore size distribution, more suitable porosity, and more suitable for the positive electrode or negative electrode can be prepared, and a porous network structure binder can be obtained, and the binder is in full contact with the active material and the conductive agent, thereby improving the adhesion strength of the thick electrode and significantly reducing the electronic conductivity between the active material, the conductive agent and the binder. In addition, the pore structure formed by the appropriate ratio of binder and conductive agent is conducive to the liquid phase transmission of the electrolyte, reduces the resistance of the thick electrode, and improves the rate performance and cycle performance. If the content of the pore former is too low, it is difficult to achieve uniform pore formation and form porous binder particles, the thick electrode has high tortuosity, the transmission resistance of the electrolyte is large, and the battery rate performance and cycle performance are significantly attenuated. If the pore-forming agent content is too high, the porous binder particles will be small and the strength of the porous network structure of the binder will be low, which will significantly reduce the adhesion strength between the binder and the active material and the conductive agent. In addition, the high binder content significantly reduces the compaction density of the thick electrode, making it easier to soften and fuse during heat treatment, which is not conducive to obtaining a thick electrode with low tortuosity.
[0037] As a preferred technical solution of the preparation method of the present invention, the granulation method in step (1) includes spray drying, and granulation and drying are performed by spray drying to prepare a porous binder with good morphology and porous structure.
[0038] Preferably, the outlet temperature of the spray drying is 150-200°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C.
[0039] Preferably, a solvent is added during the mixing of the electrode binder and the pore-forming agent in step (1).
[0040] It should be noted that a solvent is added during the mixing process of the electrode binder and the pore-forming agent to form a binder glue. When the low-tortuosity thick electrode is the positive electrode, the solid content of the binder glue is 5 to 10%, for example, it can be 5%, 6%, 7%, 8%, 9% or 10%; when the low-tortuosity thick electrode is the negative electrode, the solid content of the binder glue is 1 to 5%, for example, it can be 1%, 2%, 3%, 4% or 5%; according to the different solubility of the electrode binder in their respective solvents, the binder glue has different solid contents.
[0041] Preferably, the solvent includes any one of deionized water, N-methylpyrrolidone (NMP), and dimethyl sulfoxide (DMSO), or a combination of at least two thereof.
[0042] It should be noted that those skilled in the art can select a suitable solvent to dissolve the electrode binder according to the type of electrode binder. For example, when the electrode binder is PVDF, the solvent can be N-methylpyrrolidone, and when the electrode binder is SBR and CMC, the solvent can be deionized water.
[0043] Preferably, the pore-forming agent in step (1) comprises any one of ethanol, oxalic acid, ammonium bicarbonate, ammonium carbonate, urea and ammonium chloride, or a combination of at least two thereof, such as a combination of ethanol and oxalic acid, a combination of ammonium bicarbonate and ammonium carbonate, a combination of urea and ammonium chloride, or a combination of ethanol, ammonium bicarbonate, urea and ammonium chloride, etc.
[0044] As a preferred technical solution of the preparation method of the present invention, the dry mixing method in step (2) is dry ball milling, and a uniformly dispersed mixed dry powder is obtained by dry ball milling.
[0045] Preferably, a conductive agent is also added during the dry mixing process in step (2).
[0046] Preferably, after the coating in step (2) and before the heat treatment in step (3), a rolling operation is performed to obtain a thick electrode with a desired compaction density.
[0047] In the present invention, rolling is performed first and then heat treatment is performed, which is beneficial to pre-compact the porous binder and the electrode active material, conductive agent and other components to improve the compactness between the materials, and then heat treatment is performed to make the porous binder play a better role.
[0048] As a preferred technical solution of the preparation method of the present invention, the temperature of the heat treatment in step (3) is 100-200°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc.
[0049] Preferably, the heat treatment time in step (3) is 5 to 30 min, for example, it can be 5 min, 6 min, 8 min, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min.
[0050] In the present invention, by regulating the temperature of the heat treatment, the bonding effect between the porous binder and the electrode active material, the conductive agent and the current collector can be further improved, and a continuous channel structure can be formed in the thick electrode, which significantly reduces the tortuosity of the thick electrode and further improves the rate performance and cycle performance of the low-tortuosity thick electrode. When the heat treatment temperature is low, it is difficult for the porous binder to fully soften, and the bonding between the binder and the conductive agent and the electrode active material is affected; when the heat treatment temperature is high, it is easy to cause the porous binder to melt excessively, thereby causing part of the channel structure to collapse, affecting the electrolyte liquid phase transmission efficiency and the rate performance of the electrode.
[0051] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:
[0052] (1) mixing an electrode binder, a pore-forming agent and a solvent, and spray drying the mixture to obtain a porous binder;
[0053] (2) dry-milling the electrode active material, the porous binder and the conductive agent of step (1) to obtain a mixed dry powder, and coating the mixed dry powder on at least one side of the current collector to obtain a thick electrode precursor;
[0054] (3) The thick electrode precursor of step (2) is heat treated at 100-200° C. for 5-30 min to obtain a low-tortuosity thick electrode.
[0055] In a third aspect, the present invention provides a lithium-ion battery, wherein the positive electrode and / or negative electrode of the lithium-ion battery adopts the low-tortuosity thick electrode according to the first aspect.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The thick electrode of the present invention contains a porous binder. First, the porous binder is evenly distributed in the active coating layer, and can form uniform pores after heat treatment, and the pores are uniformly formed; second, the binder with a porous structure is fully in contact with materials such as electrode active materials after hot melting, and there is no binder migration, which can significantly improve the electrode sheet peeling strength and improve the cycle performance of the thick electrode; third, the porous binder can form a continuous through-hole structure, significantly reduce the tortuosity of the thick electrode, and improve the liquid phase transmission efficiency of the electrolyte; fourth, the porous binder can improve the mixing uniformity with the electrode active material, and the evenly mixed porous binder, electrode active material and evenly distributed pores can significantly reduce the internal resistance of the battery and improve the rate performance of the low-tortuous thick electrode. The low-tortuous thick electrode finally prepared has both good rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 It is a schematic diagram of the preparation process of a low-tortuosity thick electrode in a specific embodiment of the present invention.
[0059] Figure 2 It is a comparison diagram of the tortuosity of the pole pieces in Examples 1-3 of the present invention and Comparative Examples 1-3.
[0060] Figure 3 It is a comparison chart of the rate performance of the lithium ion batteries in Examples 1-3 of the present invention and Comparative Examples 1-3.
[0061] Figure 4 It is a comparison chart of the cycle performance of the lithium ion batteries in Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0062] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0063] Example 1
[0064] The present embodiment provides a low-tortuosity thick electrode for a positive electrode, the low-tortuosity thick electrode comprising a current collector and an active coating layer arranged on both sides of the current collector, the active coating layer comprising an electrode active material lithium iron phosphate (LFP), a carbon black (SP) conductive agent, a carbon nanotube (CNT) conductive agent and a porous binder PVDF colloid in a mass ratio of 96%:0.8%:0.7%:2.5%, the median particle size of the PVDF colloid is 15μm, and the single-sided thickness of the active coating layer is 400μm.
[0065] This embodiment also provides a method for preparing the above-mentioned low-tortuosity thick electrode, the flow chart is as follows Figure 1 As shown, including:
[0066] (1) Preparation of porous binder particles: PVDF, ammonium bicarbonate and NMP were mixed and dispersed with stirring, wherein the mass ratio of PVDF to ammonium bicarbonate was 90:10, to obtain a binder solution with a solid content of 8%, and the binder solution was granulated and cured by spray drying at a temperature of 180° C. to obtain PVDF particles with a median particle size of 15 μm;
[0067] (2) Ball milling and dry coating: Lithium iron phosphate, SP, CNT and PVDF particles obtained in step (1) are ball milled to obtain a uniformly mixed dry powder, and the mixed dry powder is dry coated on the surface of the aluminum current collector using a roller coater, with a single-side coating thickness of 400 μm, to obtain a thick electrode precursor;
[0068] (3) Electrode sheet rolling: The thick electrode precursor obtained in step (2) is rolled, and the compaction density after rolling is 2.4 g / cm 3 ;
[0069] (4) Heat treatment: The thick electrode precursor after rolling in step (3) is heat treated at a temperature of 185° C. for 10 min to obtain a low tortuosity thick electrode.
[0070] Example 2
[0071] In addition to replacing lithium iron phosphate with lithium nickel cobalt manganese oxide, the single-sided thickness is replaced with 300μm and the compaction density is replaced with 3.5g / cm 3 Except for this, the rest are the same as in Example 1.
[0072] Example 3
[0073] The present embodiment provides a low-tortuosity thick electrode for a negative electrode, the low-tortuosity thick electrode comprising a current collector and an active coating layer arranged on both sides of the current collector, the active coating layer comprising electrode active material graphite, SP conductive agent and porous binder in a mass ratio of 95.5%:1.0%:1.5%:2.0%, the median particle size of the porous binder is 10μm, and the single-sided thickness of the active coating layer is 250μm.
[0074] This embodiment also provides a method for preparing the above-mentioned low-tortuosity thick electrode, the flow chart is as follows Figure 1 As shown, including:
[0075] (1) Preparation of porous binder particles: CMC, SBR, ammonium carbonate and deionized water were mixed and dispersed by stirring, wherein the mass ratio of CMC, SBR and ammonium carbonate was 15:20:0.5, to obtain a binder glue solution with a solid content of 5%, and the binder glue solution was granulated and solidified by spray drying at a temperature of 160° C. to obtain a porous binder with a median particle size of 10 μm;
[0076] (2) Ball milling and dry coating: Graphite, SP and the porous binder obtained in step (1) are ball milled and dispersed to obtain a uniformly mixed dry powder, and the mixed dry powder is dry coated on the surface of the copper current collector using a roller coater, with a single-side coating thickness of 250 μm, to obtain a thick electrode precursor;
[0077] (3) Electrode sheet rolling: The thick electrode precursor obtained in step (2) is rolled, and the compaction density after rolling is 1.5 g / cm 3 ;
[0078] (4) Heat treatment: The thick electrode precursor after rolling in step (3) is heat treated at a temperature of 190° C. for 15 min to obtain a low tortuosity thick electrode.
[0079] Example 4
[0080] Except that the mass ratio of PVDF to ammonium bicarbonate in step (1) is 97:3, the rest is the same as Example 1.
[0081] Example 5
[0082] Except that the mass ratio of PVDF to ammonium bicarbonate in step (1) is 77:23, the rest is the same as Example 1.
[0083] Example 6
[0084] Except that the mass ratio of CMC, SBR and ammonium carbonate in step (1) is 15:20:0.14, the rest is the same as Example 3.
[0085] Example 7
[0086] Except that the mass ratio of CMC, SBR and ammonium carbonate in step (1) is 15:20:1.5, the rest is the same as Example 3.
[0087] Example 8
[0088] Except that the heat treatment temperature in step (4) is 80°C, the rest is the same as Example 1.
[0089] Example 9
[0090] Except that the heat treatment temperature in step (4) is 220°C, the rest is the same as Example 1.
[0091] Comparative Example 1
[0092] This comparative example provides a lithium iron phosphate thick electrode for a positive electrode, which is consistent with Example 1 except that the porous binder is replaced by a conventional PVDF binder and the thick electrode is prepared by a conventional slurry coating method.
[0093] The preparation method of the lithium iron phosphate thick electrode of this comparative example comprises:
[0094] PVDF and NMP are mixed, stirred and dispersed to obtain a binder slurry, and then lithium iron phosphate, SP and CNT are added and stirred and dispersed to obtain a positive electrode slurry. The content of each solid component in the positive electrode slurry is the same as the content of each component in the mixed dry powder in Example 1; the positive electrode slurry is coated on the surface of the aluminum current collector with a single-sided coating thickness of 400 μm, and roller pressing is performed to obtain a thick iron phosphate electrode.
[0095] Comparative Example 2
[0096] This comparative example provides a thick nickel cobalt lithium manganese oxide electrode for a positive electrode, which is consistent with Example 2 except that the porous binder is replaced by a conventional PVDF binder and the thick electrode is prepared by a conventional slurry coating method.
[0097] The preparation method of the nickel cobalt manganese oxide thick electrode in this comparative example is the same as that in comparative example 1.
[0098] Comparative Example 3
[0099] This comparative example provides a graphite thick electrode for a negative electrode, which is consistent with Example 3 except that the porous binder is replaced by conventional CMC and SBR binders and the thick electrode is prepared by conventional slurry coating.
[0100] The preparation method of the graphite thick electrode of this comparative example comprises:
[0101] CMC and deionized water are stirred and dispersed to obtain CMC glue, and then graphite, SP, and SBR are added and stirred and dispersed to obtain a negative electrode slurry. The content of each solid component in the negative electrode slurry is the same as the content of each component in the mixed dry powder in Example 3; the negative electrode slurry is coated on the surface of the copper current collector with a single-sided coating thickness of 250 μm, and roller pressing is performed to obtain a graphite thick electrode.
[0102] Comparative Example 4
[0103] Except that the preparation method of the thick electrode in this comparative example is replaced by the preparation method in comparative example 1, that is, the thick electrode is prepared by conventional slurry coating, the rest is the same as that in Example 1.
[0104] Comparative Example 5
[0105] Except that no heat treatment is performed, the rest is the same as Example 1.
[0106] 1. Assembly of lithium-ion batteries
[0107] The thick electrodes prepared in the embodiments of the present invention and the comparative examples are prepared into pole pieces through die cutting and slitting processes, wherein the thick electrodes used as positive electrodes (embodiments 1-2, 4-5, 8-9, comparative examples 1-2, 4-5) use graphite as negative electrodes, and the thick electrodes used as negative electrodes (embodiment 3, 6-7, comparative example 3) use lithium iron phosphate as positive electrodes, 1MLiPF6 (EC:DMC:EMC=3:5:2) as electrolyte, and the lamination and injection processes are carried out to obtain lithium ion batteries.
[0108] 2. Performance Test
[0109] (1) Tortuosity test
[0110] Symmetric cells were used to test the tortuosity of thick electrodes. The die-cut positive or negative electrodes were assembled into a single-sided symmetrical cell, and 1M LiPF6 (EC:DMC:EMC=3:5:2) electrolyte was injected, and then the cells were left standing at 45°C for 48 hours. The symmetrical cells were subjected to EIS test with a voltage amplitude of 5 mV and a scanning frequency of 10 kHz to 0.01 Hz. The test results are shown in Table 1 and Figure 2 shown.
[0111] (2) Rate performance test
[0112] At 25°C, the capacity retention rates of the batteries prepared in the embodiments and comparative examples at different rates were tested. The voltage range of the battery whose electrode active material is lithium iron phosphate is 2.5-3.65V, the voltage range of lithium nickel cobalt manganese oxide is 2.5-4.2V, and the voltage range of graphite is 2.5-3.65V. The rates are 0.5C, 1C, 2C and 3C, respectively. The capacity retention rate is calculated by dividing the capacity of XC by the capacity of 0.33C (X is 0.5, 1, 2 or 3) to obtain the capacity retention rate at the corresponding rate. The test results are shown in Tables 1 and Figure 3 shown.
[0113] (3) Cyclic performance test
[0114] Under the same temperature and voltage range as (2), the battery was subjected to 1C / 1C cycle test, and the capacity retention rate data after 100 cycles, 300 cycles and 500 cycles were obtained. The test results are shown in Tables 1 and Figure 4 shown.
[0115] Table 1
[0116]
[0117] From the above Examples 1-9, it can be seen that the thick electrode of the present invention contains a porous binder, and the binder with a porous structure can improve the mixing uniformity with the electrode active material, reduce the internal resistance, and improve the rate performance. Moreover, after heat treatment, it is in full contact with the electrode active material, and there is no binder migration, which can improve the peel strength of the electrode sheet; at the same time, the porous binder can form uniform pores and uniform pore formation after heat treatment. The continuous through-hole structure formed by it can significantly reduce the tortuosity of the thick electrode and improve the liquid phase transmission efficiency of the electrolyte. The prepared low-tortuous thick electrode has good rate performance and cycle performance.
[0118] Figure 2 , Figure 3 and Figure 4 The tortuosity, rate performance and cycle performance comparison diagrams of the thick electrodes in Examples 1-3 of the present invention and Comparative Examples 1-3 are shown in FIG. Figure 2-4 It can be seen that the thick electrode prepared by the porous binder of the present invention has a uniformly distributed binder, electrode active material, conductive agent and porous structure, the internal resistance of the battery is significantly reduced, and the rate performance and cycle performance are significantly improved. It has good applicability in both the positive electrode and the negative electrode, or in different electrode active materials such as lithium iron phosphate, lithium nickel cobalt manganese oxide and graphite. Comparative Example 1 replaces the porous binder in Example 1 with a conventional PVDF binder, that is, directly uses the binder that is not combined with the pore-forming agent in Example 1. Although other raw materials, thickness, and compaction density are the same as those in Example 1, its tortuosity is significantly higher than that in Example 1, the liquid phase transmission efficiency of the electrolyte is too poor, and the internal resistance of the battery is large. Its capacity retention rate at different rates and different number of cycles is significantly worse than that of Example 1, and the rate performance and cycle performance are significantly reduced; Comparative Example 2-3 is similar, and the tortuosity of Comparative Example 2-3 is also significantly higher than that of Example 2-3, and the rate performance and cycle performance are significantly worse than those of Example 2-3.
[0119] By comparing Example 1 with Example 4-5, and Example 3 with Example 6-7, it can be seen that the ratio between the electrode binder and the pore former will affect the structure of the prepared porous binder, thereby affecting the electrochemical performance of the low-tortuosity thick electrode. The low content of the pore former in Example 4 and Example 6 will lead to an increase in the tortuosity of the thick electrode, an increase in the resistance of the thick electrode, and a significant attenuation of its rate performance and cycle performance; the high content of the pore former in Example 5 and Example 7 will lead to a weakening of the interface contact between the binder and the active particles and the conductive agent, and the binder is easy to fuse and clog during heat treatment, the tortuosity of the thick electrode increases, the internal resistance increases, and the rate performance and cycle performance deteriorate; therefore, the low-tortuosity thick electrode in Example 1 and Example 3 has better rate performance and cycle performance.
[0120] By comparing Example 1 with Examples 8-9 and Comparative Example 5, it can be seen that the temperature of the heat treatment in the present invention affects the electrochemical properties of the low-tortuosity thick electrode. The temperature of the heat treatment in Example 8 is relatively low, which affects the softening of the porous binder, resulting in a decrease in the contact strength between the binder and the active material and the conductive agent, a significant increase in the internal resistance of the thick electrode, and degradation of the rate performance and cycle stability; the temperature of the heat treatment in Example 9 is relatively high, the melting degree of the porous binder is relatively high, the porous structure is affected, the tortuosity of the thick electrode increases, and the rate performance and cycle performance also deteriorate; in Comparative Example 5, no heat treatment is performed, the porous binder cannot fully contact the electrode active material, the conductive agent, etc., the peel strength of the electrode sheet is low, and the cycle performance and rate performance are reduced; therefore, the thick electrode in Example 1 has higher rate performance and cycle performance.
[0121] By comparing Example 1 with Comparative Example 4, it can be seen that the dry mixing and coating in the present invention can maintain the specific morphology of the porous binder and ensure the porous structure in the binder. In Comparative Example 4, the conventional slurry coating method is adopted, the porous binder will dissolve in the solvent, the pores will collapse, and a coherent pore structure cannot be effectively formed in the thick electrode. The tortuosity of the thick electrode is high, the liquid phase transmission efficiency of the electrolyte is low, and the cycle performance and rate performance of the prepared thick electrode are significantly reduced.
[0122] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A low tortuosity thick electrode with a tortuosity not exceeding 4.3, characterized in that: The low-tortuosity thick electrode comprises a current collector and an active coating layer disposed on at least one side of the current collector, wherein the active coating layer comprises an electrode active material and a porous binder; The porous binder can form a continuous and penetrating pore structure inside the active coating layer; The low tortuosity thick electrode is prepared by the following method, which comprises: (1) mixing an electrode binder, a pore-forming agent and a solvent, and granulating the mixture to prepare a porous binder; The low-tortuosity thick electrode is a positive electrode, and the mass of the pore-forming agent accounts for 5-20% of the total mass of the electrode binder and the pore-forming agent; the low-tortuosity thick electrode is a negative electrode, and the mass ratio of the electrode binder to the pore-forming agent is (25-50):(0.2-1); (2) dry-mixing the electrode active material and the porous binder described in step (1) to obtain a mixed dry powder, and coating the mixed dry powder on at least one side surface of a current collector to obtain a thick electrode precursor; (3) subjecting the thick electrode precursor of step (2) to a heat treatment at a temperature of 100 to 200° C. to obtain a low-tortuosity thick electrode; After the coating in step (2) and before the heat treatment in step (3), a rolling operation is also performed.
2. The low tortuosity thick electrode according to claim 1, characterized in that: The thickness of the active coating layer on one side is 100-1000 μm.
3. The low tortuosity thick electrode according to claim 1, characterized in that: The median particle size of the porous binder is 1 to 50 μm.
4. The low tortuosity thick electrode according to claim 1, characterized in that: The electrode active material includes a positive electrode active material or a negative electrode active material.
5. The low tortuosity thick electrode according to claim 1, characterized in that: The active coating layer also includes a conductive agent.
6. A method for preparing a low-tortuosity thick electrode according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) mixing an electrode binder, a pore former and a solvent, and granulating the mixture to obtain a porous binder; The low-tortuosity thick electrode is a positive electrode, and the mass of the pore-forming agent accounts for 5-20% of the total mass of the electrode binder and the pore-forming agent; the low-tortuosity thick electrode is a negative electrode, and the mass ratio of the electrode binder and the pore-forming agent in step (1) is (25-50):(0.2-1); (2) dry-mixing the electrode active material and the porous binder described in step (1) to obtain a mixed dry powder, and coating the mixed dry powder on at least one side surface of a current collector to obtain a thick electrode precursor; (3) subjecting the thick electrode precursor of step (2) to a heat treatment at a temperature of 100 to 200° C. to obtain a low-tortuosity thick electrode; After the coating in step (2) and before the heat treatment in step (3), a rolling operation is also performed.
7. The preparation method according to claim 6, characterized in that: The low-tortuosity thick electrode is a positive electrode, and the electrode binder includes polyvinylidene fluoride.
8. The preparation method according to claim 6, characterized in that: The low-tortuosity thick electrode is a negative electrode, and the electrode binder includes any one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, guar gum and sodium alginate, or a combination of at least two of them.
9. The preparation method according to claim 8, characterized in that: The low-tortuosity thick electrode is a negative electrode, the electrode binder comprises sodium carboxymethyl cellulose and styrene-butadiene rubber, and the mass ratio of the sodium carboxymethyl cellulose, styrene-butadiene rubber and pore-forming agent is (10-20):(15:30):(0.2-1).
10. The preparation method according to claim 6, characterized in that: The granulation method in step (1) includes spray drying.
11. The preparation method according to claim 6, characterized in that: The solvent in step (1) includes any one of deionized water, N-methylpyrrolidone, and dimethyl sulfoxide, or a combination of at least two thereof.
12. The preparation method according to claim 6, characterized in that: The pore-forming agent in step (1) includes any one of ethanol, oxalic acid, ammonium bicarbonate, ammonium carbonate, urea and ammonium chloride, or a combination of at least two of them.
13. The preparation method according to claim 6, characterized in that: The dry mixing method in step (2) is dry ball milling.
14. The preparation method according to claim 6, characterized in that: A conductive agent is also added during the dry mixing process in step (2).
15. The preparation method according to claim 6, characterized in that: The heat treatment time in step (3) is 5 to 30 minutes.
16. The preparation method according to claim 6, characterized in that: The preparation method comprises: (1) mixing an electrode binder, a pore-forming agent and a solvent, and spray drying the mixture to obtain a porous binder; (2) dry-milling the electrode active material, the porous binder and the conductive agent of step (1) to obtain a mixed dry powder, and coating the mixed dry powder on at least one side of the current collector to obtain a thick electrode precursor; (3) The thick electrode precursor of step (2) is heat treated at 100-200° C. for 5-30 min to obtain a low-tortuosity thick electrode.
17. A lithium ion battery, characterized in that: The positive electrode and / or negative electrode of the lithium-ion battery adopts the low-tortuosity thick electrode according to any one of claims 1 to 5.
Citation Information
Patent Citations
Lithium ion battery negative film and preparation method thereof
CN104157827A
Pore-forming roller, method for improving porosity of pole piece and application of pore-forming roller
CN114273510A
Binder particle aggregate for electrochemical element electrode, slurry composition for electrochemical element electrode, method for manufacturing these, electrode for electrochemical element, and electrochemical element
CN109075345A
Adhesive, preparation method thereof and slurry
CN114520329A
Dry method electrode preparation method
CN114784220A
Cited By
Low-concentration electrolyte and method for improving wettability of electrolyte
CN121331937A